2021
DOI: 10.1007/s11858-020-01216-z
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics teacher learning to notice: a systematic review of studies of video-based programs

Abstract: Teacher noticing has become increasingly acknowledged as a fundamental aspect of teacher professional competence. Teacher education scholars have examined how the development of noticing might be supported both in initial teacher education and in professional development. In mathematics teacher education, several studies have explored the use of video as a supporting tool for teacher noticing. It remains unclear how this body of work builds on the various theoretical perspectives of noticing prevalent in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 50 publications
2
86
0
22
Order By: Relevance
“…Van Es et al (2019) analyzed video-based learning environments for teachers and identified five intended goals for the use of videos, which are not distinct: "developing specialized content knowledge for mathematics teaching, learning to systematically reflect on instructional practice, improving both the quality of mathematics instruction and teachers' noticing practices for teaching, and developing a professional vision of ambitious teaching" (p. 26). In a meta-study, which was not limited to the noticing context, Santagata et al (2021) identified two types of activities, which involve watching videos, from a noticing perspective: "selective attention and knowledge-based reasoning" (p. 120). For an overview of video-based studies that foster noticing competencies, see Santagata et al (2021) or Llinares and Chapman (2020).…”
Section: Measuring (Prospective) Teachers' Noticing Competenciesmentioning
confidence: 99%
See 3 more Smart Citations
“…Van Es et al (2019) analyzed video-based learning environments for teachers and identified five intended goals for the use of videos, which are not distinct: "developing specialized content knowledge for mathematics teaching, learning to systematically reflect on instructional practice, improving both the quality of mathematics instruction and teachers' noticing practices for teaching, and developing a professional vision of ambitious teaching" (p. 26). In a meta-study, which was not limited to the noticing context, Santagata et al (2021) identified two types of activities, which involve watching videos, from a noticing perspective: "selective attention and knowledge-based reasoning" (p. 120). For an overview of video-based studies that foster noticing competencies, see Santagata et al (2021) or Llinares and Chapman (2020).…”
Section: Measuring (Prospective) Teachers' Noticing Competenciesmentioning
confidence: 99%
“…In a meta-study, which was not limited to the noticing context, Santagata et al (2021) identified two types of activities, which involve watching videos, from a noticing perspective: "selective attention and knowledge-based reasoning" (p. 120). For an overview of video-based studies that foster noticing competencies, see Santagata et al (2021) or Llinares and Chapman (2020). Amador (2019) reports that if noticing is used as a pedagogical tool, it is often also used as an analytical tool in the same project.…”
Section: Measuring (Prospective) Teachers' Noticing Competenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…A wealth of empirical studies point out that teachers' professional noticing can be promoted through specific programs in initial teacher education or professional development (Star & Strickland, 2008). Recently, many video-based programs, which aim to foster teachers' professional noticing, were developed and show considerable progress of prospective and practicing teachers' noticing, particularly concerning the attending and interpreting/reasoning facets of noticing (for a literature survey see Santagata et al, 2021). It is not an unexpected result that specific intervention activities, which offer--at least prospective--teachers the chance to use their academically acquired knowledge in learning environments, promote professional noticing, especially, when they are supported by video-based activities.…”
Section: Domain Specificity Of Noticing: Division Of Fractionsmentioning
confidence: 99%